Filamented ion tail structures at Titan: A hybrid simulation study. (November 2015) - Feyerabend, Moritz; Simon, Sven; Motschmann, Uwe; Liuzzo, Lucas
Abstract: This study investigates the processes that lead to the detection of split signatures in ion density during several crossings of the Cassini spacecraft through Titan's mid-range plasma tail (T9, T63, and T75). During each of these flybys, the Cassini Plasma Spectrometer detected Titan's ionospheric ion population twice; i.e., the spacecraft passed through two spatially separated regions where cold ions were detected, with the regions also being dominated by ions of different masses in the case of T9. Whether this filamented tail structure is an omnipresent feature of Titan's plasma interaction or a result of non-stationary upstream conditions during specific flybys is still unclear. To explain these features, we apply the hybrid simulation code AIKEF (kinetic ions and fluid electrons). Our model includes chemical reactions as well as a realistic photoionization model for a sophisticated description of the ionospheric composition of Titan. Our simulations show that the filamentation of Titan's tail is indeed a common feature of the moon's plasma interaction. Light ionospheric species escape along draped magnetic field lines to form a parabolically shaped filament structure, which is mainly seen in planes that contain the upstream magnetospheric magnetic field and the upstream flow direction. In addition, transport of ions of all species from the ramside towards downstream produces a cone structure behind Titan, with a region of decreased density inside and filaments of 1–2 R T ( R T =2575 km) thickness and enhanced density at the surface of the cone. Spacecraft trajectories that penetrate these structures allow for the detection of split signatures in the tail. The orientation of the upstream magnetic field and plasma flow as well as local time effects (i.e., Titan's orbital position) influence the location of the filaments in the tail and can also cause asymmetries in their sizes and densities. The detection of the split signatures along a spacecraft trajectory may therefore be made possible or completely prevented by moving the narrow filaments in or out of the way of the spacecraft. Our results imply that the detections of split signatures during T9, T63 and T75 are consistent by Cassini penetrating through parts of these filament structures. Abstract : Highlights: Hybrid simulations of Titan's plasma interaction. Sophisticated photoionization and statistical chemistry model. Insight in the formation of filamented density structures in Titan's plasma tail. Possible explanations for the split signatures during T9, T63, and T75.